PENGENALAN AKSES KE PERBANKAN SYARIAH MELALUI PENGEMBANGAN EKONOMI KREATIF MASYARAKAT DI DESA CIBUNIAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Widia Afria Nurlaelia; Tubagus Rifqy Thantawi; Miftakhul Anwar (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract The creative economy can be said as the creation of added value based on ideas born from the creativity of human resources and based on the use of science, including cultural and technological heritage. Cibunian village precisely in Kampung Muara Legok has minimal business actors, the average population there only relies on farming as their livelihood, while there is a lot of natural potential that can be developed if it can be managed properly. The purpose of this service is to assist the community in Cibunian Village, precisely in Kampung Muara Legok in managing kolang kaling into traditional food of kolang kaling crackers, as an effort to improve the community's economy where kolang kaling can be found easily in the village. This service uses the ESD (Education for Sustainable Development) method, which is a learning method to support sustainable development, which is a type of learning that provides awareness of an innovative and creative entrepreneurial spirit. The programs carried out include: 1) Counseling to improve the entrepreneurial spirit, 2) Training in managing traditional kolangkaling crackers, 3) Packaging/labeling training so that packaging becomes more attractive 4) Product marketing. The result of this service activity is the growing awareness of the people of Cibunian Village, precisely in Kampung Muara Legok has an independent entrepreneurial spirit. Keywords: Creative economy, traditional food, empowerment.